2020
DOI: 10.37043/jura.2016.8.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Rental Income and Cap Rates: A Comparison of the Lisbon and Porto Housing Markets

Abstract: The goal of this article is to analyse the relationship between rental income and capitalisation rates when real estate value is assessed in parishes of the Lisbon and Porto municipalities. Based on housing market values in euros per square metre during the 2006-2009 period, the income approach was used to compare the two main types of apartments (i.e. B2, or two-bedroom, and B1, or one-bedroom) in Lisbon and Porto. We used the capital asset pricing model to calculate the risk measure. The cluster analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Another approach to avoiding the residual autocorrelation is to forecast single point-in-time metrics as done in Moreira et al (2016). This micro-level study successfully identified over-investment in a neighbourhood of Portugal by creating a multivariate regression of a single period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another approach to avoiding the residual autocorrelation is to forecast single point-in-time metrics as done in Moreira et al (2016). This micro-level study successfully identified over-investment in a neighbourhood of Portugal by creating a multivariate regression of a single period.…”
Section: Literature Reviewmentioning
confidence: 99%